2002
DOI: 10.1080/000163502760148016
|View full text |Cite
|
Sign up to set email alerts
|

Salivary variables in relation to tobacco smoking and female sex steroid hormone-use in 30 to 59-year-old women

Abstract: Several systemic conditions may have an influence on oral health. Hormone replacement therapy (HRT) has a positive effect on alveolar bone of menopausal women and smoking a negative effect. However, little is known about their effect on saliva. The purpose of this study was to examine the effect of hormone-use and tobacco smoking on the composition of saliva, in particular on the inorganic constituents. Salivary samples were collected from a representative study group comprising 1,013 women (30-59 years) parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…After the abstract review, 52wereexcluded(Appendix 2) and 15 were retrieved as full text and assessed for eligibility (after duplicate removal). Ten studies [17][18][19][20][21][22][23][24][25][26] were subsequently excluded as the eligibility criteria were not respected; see Appendix 4 for reasons for exclusion. No additional study was identified by checking reference lists of retrieved studies and this reference list check highlighted a large number of duplicates with database search results.…”
Section: Summary Measuresmentioning
confidence: 99%
“…After the abstract review, 52wereexcluded(Appendix 2) and 15 were retrieved as full text and assessed for eligibility (after duplicate removal). Ten studies [17][18][19][20][21][22][23][24][25][26] were subsequently excluded as the eligibility criteria were not respected; see Appendix 4 for reasons for exclusion. No additional study was identified by checking reference lists of retrieved studies and this reference list check highlighted a large number of duplicates with database search results.…”
Section: Summary Measuresmentioning
confidence: 99%
“…[26] The increased salivary total protein in diabetics could be attributed to the increase in basement membrane permeability, allowing easy and increased passage of serum proteins into the whole saliva via salivary gland and gingival crevices. [232728] Arati et al . and Streckfus et al .…”
Section: Discussionmentioning
confidence: 99%
“…65 Although there is little data on the relationship between oral health and ions present in saliva, the salivary electrolyte levels are determined by general health. [66][67][68][69][70][71][72] Calcium (Ca) and phosphorus (P) ions, in addition to participating in the remineralization of dental hard tissues (along with sodium (Na) and magnesium (Mg) ions), contribute to plaque mineralization and tartar formation. [73][74][75][76] A similar function is performed by fluorine (F), which binds to the amino groups in hydroxyapatite and replaces hydroxide ions to form fluorapatite, which is more resistant to acids produced by bacteria and contained in food.…”
Section: Effect Of Smoking On the Salivary Mineral Contentmentioning
confidence: 99%